Development of a Service Quality Analysis Information System with the Importance Performance Analysis Method - Riyan Saputra; Firna Yenila; Sepsa Nur Rahman (Journal of Computer Scine and Information Technology, 2023)
Service is an activity where a company helps customers solve their problems. Good service quality can make customers loyal to the company. To maintain service quality, service performance is measured. The Importance Performance Analysis (IPA) method is one method that can be used to measure service performance from a customer perspective. Qanaah Carpet Shop is a business that operates in the field of goods and services. By using the IPA method, Toko Qanaah Karpet measures its service performance manually using paper media, which makes analysis ineffective and inefficient. This research aims to build an information system that can analyze service quality using the IPA method. The analysis was carried out by measuring 30 service attributes which were divided into 5 dimensions, namely: Tangible (Physical evidence), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Guarantee), and Empathy (Empathy). Data collected through a questionnaire involved 50 respondents. The results of this research show that there are 6 attributes in quadrant A, 10 attributes in quadrant B, 8 attributes in quadrant C, and 6 attributes in quadrant D. Companies can take action to maintain and improve service attributes in accordance with the recommendations from the results of this research.